Treating normal early gestation placentae with preeclamptic sera produces extracellular micro and nano vesicles that activate endothelial cells. (April 2017) - Xiao, Xirong; Xiao, Fengyi; Zhao, Mingzhi; Tong, Mancy; Wise, Michelle R.; Stone, Peter R.; Chamley, Lawrence W.; Chen, Qi
Highlights: Preeclamptic sera produced placental micro- and nano vesicles activating endothelial cells. The levels of HMGB1 were increased in preeclamptic sera produced placental micro- and nano vesicles. Nifedipine or labetalol significantly prevented endothelial cell activation induced by placental EVs. Abstract: Objectives: Preeclampsia is characterised by systemic endothelial cell dysfunction thought to be triggered by toxic/dangerous factors from the placenta, including placental extracellular vesicles (EVs). Why placental EVs become toxic is unknown. We previously reported that preeclamptic sera produced toxic/dangerous placental macrovesicles but whether small EVs are also toxic/dangerous in preeclampsia is unknown. Study design: First trimester placental explants were treated with 10% preeclamptic or control sera (n = 10) for 24 h. Micro- and nano-vesicles were harvested by sequential centrifugation. Micro- or nano-vesicles were also exposed to monolayers of endothelial cells in the presence or absence of nifedipine (50 μg/ml) or labetalol (0.5 μg/ml) which are well-known anti-hypertensives in clinical practices. Main outcomes measures: The number and size of micro- and nano-vesicles were counted. Endothelial cell-surface intercellular adhesion molecule 1 (ICAM-1) and high mobility group box 1 (HMGB1) levels in micro- or nano-vesicles were measured by immunoassays. Results: Neither the amount nor size of both micro- and nano-vesicles was different after treating placental explants with preeclamptic or control sera. The levels of HMGB1 were significantly increased in both micro- and nano-vesicles from preeclamptic sera treated placental explants (p < 0.03). Exposing endothelial cells to micro- or nano-vesicles from preeclamptic sera-treated placental explants induced endothelial activation, but it was reversed by co-incubation with nifedipine (p = 0.004) or labetalol (p = 0.002). Conclusion: Our data demonstrate that preeclamptic sera produce toxic/dangerous micro- and nano-placental EVs which activated endothelial cells. This effect was reversed by antihypertensives. The increased levels of HMGB1 in EVs may contribute to endothelial cell activation.